Analysis of the triple pirouette of professional classical ballet dancers - Kawabata, M.; Ae, M.; Tsuda, H.; Horiuchi, K. (ISBS Proceedings Archive (Michigan), 2022)
Classical ballet pirouette is difficult technique to master even for professional dancers. Little research has been conducted on the pirouette. The purposes of this study were to analyse the pirouette movement of professional classical ballet dancers, and to search critical viewpoints for instruction focusing on their averaged motion (Ae et al.,2007) and motion variation of body segments. The participants were 11 professional female classical ballet dancers performed the triple pirouette. The motion capture system with 12 cameras (Qualisys, Sweden, 250 Hz) was used to collect three-dimensional coordinate data. The coefficient of variation (CV) and standard deviation of the body segments were used to represent the variability of body segment movement. There were smaller motion variations in the shank, thigh, head, and torso of the top dancers, which indicated that the similar motion patterns appeared in the triple pirouette in these segments. On the other hand, the larger variation of the left foot in the preparation and turning phase indicated that ankle adjustment may be employed to maintain balance. The upper extremity with large variation may also function as an angular momentum generator and balance adjustor and may be an indicator of difference in teaching methods.